Students’ Motivation through Problem-based Learning with a Culturally Responsive Teaching (CRT) Approach in Mathematics Lessons - Sukmanasa, Elly; Novita, Lina; Suhardi, Eka; Maesya, Aries; Awiria, Awiria; 'ala, Faridatul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
Motivation is a person's inner desire to achieve a goal. Motivation can come from within oneself or from external or environmental factors. The two types of learning motivation are extrinsic (external) and intrinsic (deep). Rewards and praise for good work are examples of extrinsic motivation. These two types of motivation work together and strongly support learning success during the learning process, teachers must pay attention to student motivation. The purpose of this study was to analyze the motivation of fourth grade students to learn mathematics with problem-based learning methods. This research was conducted by classroom action research study. Fourth grade students become subjects of this research. Data were collected through observation, interviews, and learning motivation questionnaires. The results showed that the average motivation score of students increased from cycle 1 to cycle 2. In Cycle I, the count was 66.37, but in Cycle II the count increased to 90.96. These results suggest that problem-based learning, combined with an instructive cultural approach (CRT) to the environment can significantly increase students' desire to learn as an alternative to improving student learning outcomes